ANALISIS PENGARUH LINGKUNGAN KERJA TERPERSEPSI, KOMPENSASI TERPERSEPSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN BAGIAN PRODUKSI PT.KHARISMA KLASIK INDONESIA) - AnggrainiShyntia Devi, 13.05.51.0064 (Students' Journal of Economic and Management, 2017)
This study was carried out aimed to analyze the influence impressed Work Environment, impressed Compensation, and Motivation on the performance of employees PT.Kharisma Klasik Indonesian. The sampling technique used with random sampling method, taking a sample of 100 respondents. The results of this study that indicate : 1) there is a positif and significant influence between impressed work environment variable (x1) on employee performance (Y) using T test 0,026. 2) there is a positif and significant influence between impressed compensation variable (x2) on employee performance (Y) using T test 0,013. 3) there is a positif and significant influence between motivation variable (x3) on employee performance (Y) using T test 0,000 Keywords : impressed work environment,impressed compensation, motivation and performance